MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR SISWA MELALUI MODEL PEMBELAJARAN KOOPERATIF TIPE JIGSAW PADA MATERI POKOK BAHAN KIMIA DALAM KEHIDUPAN KELAS VIII A DI SMPN 1 PARINGIN - Juni Angkowati (Universitas Lambung Mangkurat, 2013)
The research on “chemical in life” using cooperative learning model types of “Jigsaw” method was conducted. This study aims to find out students 'improvement, cognitive skills, student’s activities and responses on “Jigsaw” method. This research used class-action-research design with 2 cycles. Subjects were students of eighth grade of Junior High School 1 Paringin. Totally, there were 24 students involved on this study. Data was collected by using achievement test, questionnaires, and observations. Subsequently, data were analyzed by using percentation technique. The result showed that by using “Jigsaw” method, student’s achievments on chemical in life increased from 58,3% on the first cycle to 91,7% on the second cycle. From the first to the second cycle, student’s activities in the group improved. Students gave positive responds to the Jigsaw models. Teacher skills in implemetation Jigsaw models increased from good on the first cycle to very good category on the second cycle.Key words: Cooperative learning model types of “Jigsaw”, chemistry in life.